Awareness about Janani Suraksha Yojana among women: a community-based study - Srivastava, Sneha; K. Sureka, Ritu (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Janani Suraksha Yojana (JSY), a maternity-benefit scheme launched by GOI (Government of India) in April 2005 under the national health mission aims to lessen maternal and neonatal deaths by promoting institutional birth among underprivileged pregnant women. The current research aimed to assess pregnant and post-partum women’s awareness about JSY scheme and to examine how the various components of the scheme were utilized by them. Methods: The study followed a cross- sectional approach to collect data through in-person interviews after obtaining informed consent, using a pre-tested predesigned questionnaire. Women who were pregnant or delivered baby after the implementation of JSY were included in the study. Results: Out of the total 85 women interviewed, it was seen that more than half of the women (63.5%) had heard about the JSY programme and their source of information was from auxiliary nurse midwives (ANMs) and anganwadi workers (AWWs) (35.8%) followed by radio/ T. V. (30.6%). Less than half of the respondents (35.3%) were unaware about cash incentives offered to pregnant women in rural areas. The study also revealed that a high correlation exists between family income and respondent’s awareness about the JSY scheme. Conclusions: It was concluded from the findings that there is a dire need to improve the awareness about the utilization of JSY scheme among the urban population. Efforts should be enhanced to educate the health staff, AWWs and ASHA about the scheme as they are the agents of delivery and social change.